Politics of haunting and memory in international relations - Auchter, Jessica (London Routledge, 2014)
"International Relations has traditionally focused on conflict and war, but the effects of violence including dead bodies and memorialization practices have largely been considered beyond the purview of the field. Drawing on Jacques Derrida's notion of hauntology to consider the politics of life and death, Auchter traces the story of how life and death and a clear division between the two is summoned in the project of statecraft. She argues that by letting ourselves be haunted, or looking for ghosts, it is possible to trace how statecraft relies on the construction of such a dichotomy. Three empirical cases offer fertile ground for complicating the picture often painted of memorialization: Rwandan genocide memorials, the underexplored case of undocumented immigrants who die crossing the US-Mexico border, and the body/ruins nexus in 9/11 memorialization. Focusing on the role of dead bodies and the construction of particular spaces as the appropriate sites for memory to be situated, it offers an alternative take on the new materialisms movement in international relations by asking after the questions that arise from an ethnographic approach to the subject: viewing things from the perspective of dead bodies, who occupy the shadowy world of post-conflict international politics. This work will be of great interest to students and scholars of critical international relations, security studies, statecraft and memory studies"--
Ghostly politics : an introduction -- "We're all of us haunted and haunting" -- bones in a brown bag : haunting and the place of the body in Rwandan genocide memorialisation -- Border monuments : memory, counter-memory, and (b)ordering practices along the US-Mexico border -- Vanishing monuments : absence and 9/11 memorialisation.
Includes bibliographical references and index.
Keywords: International relations -- Psychological aspects; Memorialization -- Political aspects; Atrocities -- Political aspects; Collective memory -- Political aspects; September 11 Terrorist Attacks, 2001.; POLITICAL SCIENCE / General; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / International Relations / General; Rwanda -- History -- Civil War, 1994 -- Atrocities; Mexican-American Border Region -- Emigration and immigration -- Political aspects